Health Related Quality of life after Corrective Surgery for Congenital Heart Disease - Heusch, A.; Calaminus, G.; Kahl, J.; Schmidt, K. (Klinische Pädiatrie, 2014)
After corrective surgery for congenital heart defects (CHD) many patients suffer from residual defects, some with reduced cardiorespiratory capacity and possible impairment of their health related quality of life (HRQoL). The aim of our study is to evaluate, how children after surgery for CHD rate their HRQoL.Method: A standardised questionnaire developed for self-rating in children between 8 and 18 years and dealing with 7 different domains concerning the HRQoL (friends, family, physical functioning, cognition, body image, emotional function and autonomy) was independently answered from patients and their parents during an outpatient visit at their pediatric cardiologist throughout Germany.Results: 173 patients (40% female, 60% male, mean age 11.6 years) were interviewed, 167 questionnaires could be evaluated. The mean time interval after surgery was 9.8±3.4 years. Patient had had surgery for complete different types of CHD (ventricular septal defects n=50, Tetralogy of Fallot n=51, univentricular heart n=26, transposition of great arteries n=40). The results were compared with those of an age-matched control group (n=169). Patients with CHD reported a better HRQoL than the controls for all items (p<0.01). There was no significant gender specific difference. After puberty, the rating for most items, except of “body image“, had become very similar compared to controls. Parents assessed their children significantly worse in 3 domains (friends, body image and emotion; p<0.01). Conclusion: Children with congenital heart defects are able to develop coping structures, that enable them to live a normal life from their individual point of view. Integration in psychosocial structures seems to be rather normal when compared to healthy controls. Many patients considered their HRQoL as even better.
Keywords: health related quality; heart defect; children; congenital; parents